An ivestigation into the structure and conduct of the diploma in education correspondence course - De Silva, L.D.P. (My University, 1986)
Preparation of teachers for the profession is a matter of profound social concern. The progress, development and quality of a nation greatly depends on the teachers who give shape to the personality of the millions in the country. This calls for systematic and better thought out programmes for the accomplishment of their tasks expected of the teachers by the society. Over the past few years, the efficiency bar imposed ...